Who really drove the economy into the ditch? - Fried, Joseph (Algora Pub., 2012)
This is an opinionated book with an attitude. However, the author, a CPA and MBA, presents economic information in a conversational tone and meticulously backs up his views with references, charts, and quotes. Joseph N. Fried has published several books with Algora, explaining financial controversies and challenges for the general reader. Here, he highlights eye-popping aspects of the recent financial circus including: Drive-by house appraisals; the impact of hundreds of local housing programs funded by HUD; state governments, and housing advocacy groups; false delinquency statistics put forth.